Non-alcoholic fatty liver disease associated with hypobetalipoproteinemia: report of three cases and a novel mutation in APOB gene - Rodrigues, Joana (2016)
Background: Non-alcoholic fatty liver disease, the leading cause of chronic liver disease in children, is defined by hepatic fat infiltration >5% of hepatocytes, in the absence of excessive alcohol intake, evidence of viral, autoimmune or drug-induced liver disease. Conditions like rare genetic disorders must be considered in the differential diagnosis. Case Report: Two male brothers, and a non-related girl, all overweight, had liver steatosis. One of the brothers and the girl had elevated transaminases; all three presented with low total cholesterol, low density lipoproteins and very low density lipoproteins cholesterol levels, hypotriglyceridemia and low apolipoprotein B. A liver biopsy performed in the brother with citolysis confirmed steatohepatitis and the molecular study of apolipoprotein B gene showed a novel homozygous mutation (c.9353dup p.Asn3118Lysfs17). Patients with cytolysis lost weight, however liver steatosis persists. Conclusion: Fatty liver disease might be a consequence of hypobetalipoproteinemia. Evidence is scarce due to low number of reported cases.